2018
DOI: 10.1007/s11356-018-1980-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of size-segregated elements in diesel-biodiesel blend exhaust emissions

Abstract: This study was based on the determination of metals in particulate matter emitted by a typical diesel engine used by busses and trucks in Brazil. Emissions were sampled using a cascade impactor, and the engine was operated using diesel with 5% (B5), 10% (B10), 15% (B15), and 20% (B20) of biodiesel. The particulate matter was stratified in different sizes, i.e., 18, 5.6, 3.2, 1.8, 1.0, 0.560, 0.320, 0.180, 0.100, and 0.056 μm. Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb, V, and Zn with concentrations within 10 to 1000 ng m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The observation of mass concentrations increasing with decreasing carbon number for dicarboxylic acids (i.e., oxalate > succinate > adipate) is consistent with many past studies for other regions as larger chain acids undergo oxidative decay to eventually form oxalate (e.g., Kawamura and Ikushima, 1993;Kawamura and Sakaguchi, 1999;Sorooshian et al, 2007). Maleate is an unsaturated dicarboxylic acid emitted from gas and diesel engines (Rogge et al, 1993) and a product of the photooxidation of benzene (Kawamura and Ikushima, 1993). The aromatic dicarboxylic acid phthalate is a known photooxidation product of naphthalene and stems largely from plastic processing and fuel combustion (Fraser et al, 2003;Kautzman et al, 2010;Fu et al, 2012;Kleindienst et al, 2012).…”
Section: Water-soluble Ionssupporting
confidence: 89%
“…The observation of mass concentrations increasing with decreasing carbon number for dicarboxylic acids (i.e., oxalate > succinate > adipate) is consistent with many past studies for other regions as larger chain acids undergo oxidative decay to eventually form oxalate (e.g., Kawamura and Ikushima, 1993;Kawamura and Sakaguchi, 1999;Sorooshian et al, 2007). Maleate is an unsaturated dicarboxylic acid emitted from gas and diesel engines (Rogge et al, 1993) and a product of the photooxidation of benzene (Kawamura and Ikushima, 1993). The aromatic dicarboxylic acid phthalate is a known photooxidation product of naphthalene and stems largely from plastic processing and fuel combustion (Fraser et al, 2003;Kautzman et al, 2010;Fu et al, 2012;Kleindienst et al, 2012).…”
Section: Water-soluble Ionssupporting
confidence: 89%
“…In contrast to a previous study that depicted haze-related urban PM as spherical based on 2D SEM (Zeb et al 2018 ), we have shown using 3D confocal imaging that DPM can contain particles with sharp appearing edges. Diesel emission particles can vary in size from fine particles less than 100nm to several micrometers (Liati et al 2013 , Rocha and Corrêa 2018 ); in view of the range of DPM size, it is possible that at least some particles imaged with confocal microscopy may consist of fine particle agglomeration. A recent study has reported that brake dust particles can also have jagged edges (Selley et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…No signal was found for DJF, possibly due to the lower levels of precursors from reduced anthropogenic activity during this season. To demonstrate the importance of this process, M. T. Cruz et al (2019) attributed a significant fraction of the MOUDI aerosol mass in Metro Manila to an aged aerosol factor, consisting of multiple sources such as fuel combustion (Rocha & Corrêa, 2018), metallurgical processes (Youn et al, 2016), and biogenic emissions (Sorooshian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%